2022
DOI: 10.3390/atmos13071027
|View full text |Cite
|
Sign up to set email alerts
|

Lowering the Temperature to Increase Heat Equity: A Multi-Scale Evaluation of Nature-Based Solutions in Toronto, Ontario, Canada

Abstract: Nature-based solutions (NbS) present an opportunity to reduce rising temperatures and the urban heat island effect. A multi-scale study in Toronto, Ontario, Canada, evaluates the effect of NbS on air and land surface temperature through two field campaigns at the micro and meso scales, using in situ measurements and LANDSAT imagery. This research demonstrates that the application of NbS in the form of green infrastructure has a beneficial impact on urban climate regimes with measurable reductions in air and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…Studies have also assessed the role and effect of NbS configurations (i.e., size, shape, and proximity) in cooling urban areas [159,160]. Fewer studies [46], however, consider an integration of micro and mesoscale measurements to assess the efficacy of NbS interventions in lowering ambient and land surface temperatures.…”
Section: Sensing Methodsmentioning
confidence: 99%
“…Studies have also assessed the role and effect of NbS configurations (i.e., size, shape, and proximity) in cooling urban areas [159,160]. Fewer studies [46], however, consider an integration of micro and mesoscale measurements to assess the efficacy of NbS interventions in lowering ambient and land surface temperatures.…”
Section: Sensing Methodsmentioning
confidence: 99%
“…13,49 Heat equity refers to addressing the disproportionate exposure to heat that marginalized communities often face as a result of factors such as inadequate housing, limited access to green spaces, and limited access to cooling resources. 68,69 By ensuring that all individuals have equal access to means of protection from heat-related health risks, health systems can mitigate the negative impact of heatwaves on vulnerable communities, particularly in light of the fact that hazardous infrastructure is often located in close proximity to these marginalized communities. 70 These efforts must also be integrated and coordinated with adaptation efforts at the state and federal level.…”
Section: Adaptation and Mitigation Strategiesmentioning
confidence: 99%
“…There have been several studies of urban heat island mitigation via green spaces through spatial resolution modeling of the cooling island effect using land cover [39]. It has also been demonstrated that NbS in the form of green infrastructure can mitigate urban heat islands by lowering atmospheric and surface temperatures [40]. A wind-based architectural design method has been proposed in consideration of interactions between wind and the built environment [41].…”
Section: Topic Analysismentioning
confidence: 99%